Hypoglycemic Effect of Nigella sativa L. (Ranunculaceae) Extract in Streptozocin (STZ) Induced Diabetic Rats - Shrestha, Laxmi; Shrivastava, Amit; Joshi, Bishal; Pokhrel, Buddhi Raj; Gurung, Shanti; Rayamajhi, Nabin; Gautam, Narayan (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Diabetes mellitus is the most common metabolic disease worldwide. Nigella sativa also known as black cumin, is an emerging miracle herb with a rich historical and religious background. In the present study, we have attempted to study the hypoglycemic effect of aqueous extract of Nigella sativa on diabetes-induced rats. MATERIAL AND METHODS This preclinical study was conducted in Department of Pharmacology from August to October 2019. In this study, hyperglycemia was induced by a single intraperitoneal dose of 60 mg/kg streptozotocin in 0.1 M citrate buffer (pH 4.5). Animals were divided into five groups containing normal control, negative control, standard, test-1, and test-2. The aqueous extract of Nigella sativa was administered 400 and 800 mg/kg per oral in both the test groups for 18 days. Blood glucose level was measured at three-days interval by glucometer. Oral glucose tolerance test was done by administrating 2 gm/kg per oral glucose and the blood glucose was recorded every two-hours interval for eight hours. RESULTS An oral glucose tolerance test showed a decrease in blood glucose level at the dose of 400 and 800 mg/kg compared to the negative control group. The administration of aqueous extract of Nigella sativa for 18 days showed significant decrease in blood glucose level (p=0.001) compared to negative control group. The blood glucose level in test 1 (400 mg/kg) was significantly reduced compared to the standard group (p***<0.001). The blood glucose level in test 2 at 18th day was less significant (p*< 0.05) compared with standard group and test 1 (p**<0.01, p***<0.001). CONCLUSION The findings of the present study indicate that the aqueous extract of Nigella sativa has significant hypoglycemic effect in Wistar rats.